Detailed Exploration Of Feasibility Study Of Siskeudes Implementation In Pematasang Serai Village, Langkat District - Dito Aditia Darma Nasution; Mustafa, Mustafa; Annisa Fajariah Damanik (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to provide detailed exploratory information on feasibility studies implementation of Siskeudes in Pematasang Serai Village, Langkat Regency in the framework of realizing accountability in village fund management. The focus in this research is Role Siskeudes which is used in preparing financial reports for the Pematasang Serai Village, Langkat Regency. This study used qualitative research methods. Technique The data collection used in this research is the observation method, interviews and documentation. The data analysis technique used in this research is engineering qualitative data analysis. The data analysis component used is data reduction, data display, and drawing conclusions. The research results show that Siskeudes played an important role in making it Pematang Serai Village financial report,. Siskeudes Very make it easier for Village Officials, especially the Secretary and Head of Finance of Pematang Serai Village in preparing and inputting financial reports. Public also involved in preparing the budget for one period, represented by the Community figures who participate in every deliberation in village financial budgeting Pematang Serai Village, Langkat Regency. Financial reports available in Pematang Serai Village is good, this is based on the financial reports created as proof of the village government's responsibility to the local community as well as to regional governments.